The short Synacthen test: a questionnaire survey of current usage. Issue 10 (11th July 2012) - Elder, Charlotte Jane; Sachdev, Pooja; Wright, Neil Peter
Abstract : Background: Supported by meta-analyses, the low-dose Synacthen test (LDST) has gained in popularity, with many believing it to be more sensitive than the supraphysiological standard (250 µg) short ST (SSST), particularly when assessing children prescribed high-dose inhaled corticosteroids (HDICS). However, consensus is lacking about its specific clinical application, what is considered 'low dose' and how that dose is made up. Methods: To ascertain current use of the short Synacthen test (SST), a questionnaire was emailed to members of the British Society of Paediatric Endocrinology and Diabetes in the UK and Ireland (N=257), requesting a response from each department (N=92). A reminder was sent a month later to members of departments which had not responded. Results: The authors received 39 replies, giving a response rate of 42%. All departments use the SST: 82% use an LDST, 87% use the SSST and 69% use both. The 1 µg dose was used by 44% of hospitals, with the other 56% using seven different doses based on age, weight and body surface area. There were 14 different methods of preparing the low dose test. Additionally, variations in the timings of cortisol sampling and the diagnostic cut-offs for adrenal insufficiency were found. Increased requests for SSTs in children with asthma prescribed HDICS were noted by 44% of respondents, with 67% reporting the detection of adrenal suppression in this group. Conclusion: Standardisation of the SST is required to address the considerable variation in the methodology and application of this test in the UK and Ireland.